2010
DOI: 10.5053/ejobios.2010.4.0.7
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and anatomical investigation about two rare and endemic Crocus taxa (Iridaceae) from Southern Anatolia

Abstract: The morphological and anatomical characteristics of Crocus reticulatus subsp. hittiticus and Crocus cancellatus subsp. lycius, which are under the danger of extinction, have been investigated. The distributions of the two endemic subspecies are limited in Turkey. The plant samples were collected from the South Anatolia Region. The subsp. hittiticus flowers in the early spring whereas subsp. lycius flowers in the autumn. Their corm tunics are coarsely reticulate-fibrous. The subsp. hittiticus has blackish anthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The investigated species has xeoromorphic characters such as; thick cuticular layer on the epiderma of leaf and stem, bulliform cells on the upper epiderma of leaf, the edges of the leaves curved towards inside, stomata below than the epiderma cells, epiderma trichomes, lacking of stoma in the upper epiderma, palisade parenchyma more than spongy parenchyma, dense sclerenchyma cells in the vascular bundles and on the edge of the leaf, the the extending sclerenchyma as girders towards epiderma and the presence of bundle sheath. These chacacters were determined in Iridaceae and the other families [15,16,18,19,20,21]. Consequently, morphologic and anatomic properties of I. nezahatiae which is under threat of exctinction were determined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The investigated species has xeoromorphic characters such as; thick cuticular layer on the epiderma of leaf and stem, bulliform cells on the upper epiderma of leaf, the edges of the leaves curved towards inside, stomata below than the epiderma cells, epiderma trichomes, lacking of stoma in the upper epiderma, palisade parenchyma more than spongy parenchyma, dense sclerenchyma cells in the vascular bundles and on the edge of the leaf, the the extending sclerenchyma as girders towards epiderma and the presence of bundle sheath. These chacacters were determined in Iridaceae and the other families [15,16,18,19,20,21]. Consequently, morphologic and anatomic properties of I. nezahatiae which is under threat of exctinction were determined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…(Kandemir, 2009), C. gargaricus Herbert, C. nubigena Herbert, C. mouradii Withall and Mathew, C. candidus E. D. Clarke, C. pallasii Goldb., and C. pulchellus Herbert (Satıl and Selvi, 2007). As in the case of many other species (Kandemir, 2010;Raca et al, 2017), two out of four large vascular bundles are located in the corners of the keel and the other two are positioned at the end of the arms. Exceptions can be found in some sections from Mladenovac, Zlatibor Mt., Trebević Mt., and Kopaonik Mt.…”
Section: Discussionmentioning
confidence: 75%
“…heuffelianus with different chromosome numbers may represent independent species. The leaf anatomical characters, used together with a wide range of other diagnostic characters, are indispensable in taxonomy (Rudall and Mathew, 1990;Akan, 2007;Erol and Küçüker, 2007;Satıl and Selvi, 2007;Kandemir, 2009Kandemir, , 2010Kandemir, , 2011Kandemir, , 2012Coşkun, 2010;Özdemir, 2010;Yetişen, 2013;Candan, 2015aCandan, , 2015bRaca et al, 2017). These authors generally pointed out the relevance of leaf blade and surface, mesophyll, and vascular bundle features as good differential markers.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of morphometry is objectivity in data handling, especially when many variables are involved (Manly, 1994). In addition, studies conducted on Crocus and Iris (Kandemir, 2010;Sapir et al, 2002) showed that morphometric analyzes can be useful in clarifying systematic questions in Iridaceae. Multivariate methods have been widely used as taxonomical tools across taxonomic groups to answer different questions, including ecological influence of geography and soil parameters on morphological variability within taxa (Debussche and Thompson, 2003;Ellison et al, 2004;Pinheiro and De Barros, 2007).…”
Section: Introductionmentioning
confidence: 99%